Pengembangan bahan ajar mobile learning berbasis android terhadap kemampuan pemecahan masalah dalam materi trigonometri pada siswa kelas X SMA Negeri 1 Tumbang Titi - Dicky Adethia; Yudi Darma; Nurmaningsih Nurmaningsih (LPD IKIP PGRI Pontianak, 2022)
Learning media can represent what the teacher is unable to say through words, so that the abstractness of the material can be concretized with the presence of learning media. This research is a development research aimed at producing valid, practical and effective learning media for android applications. This study uses research and development methods. This study uses a 4-D design model. The subjects of this study were students of class X SMA Negeri 1 Tumbang Titi. Data collection techniques carried out in this study include validity, obtained through validation by the validator; practicality, obtained through questionnaires on the results of teacher and student responses to learning media; effectiveness, obtained through student learning outcomes of learning media. The results showed that the average value of the Android application learning media validity was 92.37% with very valid criteria. The practicality of the media was obtained from the results of the teacher's response questionnaire of 93.6% with practical criteria, while the results of the student response questionnaire were 97.29% with very practical criteria. The effectiveness of the media from student learning outcomes is 66.67% with effective criteria.